Implementation Of Problem-Based Learning In Sar Education And Training: A Narrative Study At Basarnas - Euis Nurmiati; Sugeng Bayu Wahyono; Muhammad Risal Rhomadan (PT Publikasiku Academic Solution, 2024)
The purpose of this study is to conduct an in-depth examination of the implementation of the problem-based learning (PBL) process through SAR (Search and Rescue education and training) experienced by Basarnas Yogyakarta members. The PBL model, which is relevant to the needs of SAR personnel, helps them face emergency situations and prepares them through realistic and learner-centered education. This research used a qualitative method with a narrative approach. The subjects of this study are 10 SAR personnel. Data were collected using observation techniques, in-depth interviews, documentation, and triangulation. The data analysis technique follows the qualitative descriptive analysis model of Matthew B. Miles, A. Michael Huberman, & Johnny Saldana, which includes data condensation, data presentation, and conclusion drawing. The findings indicate that the learning process using the PBL model through SAR training is oriented toward student-centered learning. The extensive opportunities provided by the PBL model offer direct experience that aligns with the goals of SAR training, fostering the development of problem-solving skills, teamwork, motivation, and independent learning among SAR personnel. The results of this study are expected to make a significant contribution to SAR education literature, offer practical recommendations for developing more effective and responsive SAR training curricula, and provide practical guidelines for other training institutions. The results of this research can be a basis for developing SAR training policies and curricula that are more problem-solving oriented. Basarnas may consider adopting PBL as the main approach in SAR education and training across their units.